2021
DOI: 10.1111/ijcp.14185
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum albumin/globulin ratio in combination with prognostic risk indexes of febrile neutropenia

Abstract: Objectives:The aim of this study was to evaluate the effect of the serum albumin/ globulin ratio (AGR) on the 30-day mortality of febrile neutropenia (FEN). The second aim of the study was to evaluate the effect of the combination of the AGR with the Multinational Association for Supportive Care in Cancer (MASCC) and Clinical Index of Stable Febrile Neutropenia (CISNE) risk indexes on 30-day mortality of FEN.Methods: A retrospective study evaluating the effect of serum AGR, MASCC and CISNE scores on 30-day FEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Cytohubba in Cytoscape software was used to select the top hub genes from PPI network (Figure 8A). The hub genes were fibrinogen alpha chain (FGA, MIM: 134820), fibrinogen beta chain (FGB, MIM: 134830), alpha 2‐HS glycoprotein (AHSG, MIM: 138680), albumin (ALB, MIM: 103600), alpha‐1‐microglobulin/bikunin precursor (AMBP, MIM: 176870), serpin family A member 1 (SERPINA1, MIM: 107400), apolipoprotein H (APOH, MIM: 138700), inter‐alpha‐trypsin inhibitor heavy chain 2 (ITIH2, MIM: 146640), histidine‐rich glycoprotein (HRG, MIM: 142640), and transthyretin (TTR, MIM: 176300), which mostly were serum proteins and plasma proteins, mainly functioning in coagulation, protease inhibitors, transport or inflammatory regulation 25–33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytohubba in Cytoscape software was used to select the top hub genes from PPI network (Figure 8A). The hub genes were fibrinogen alpha chain (FGA, MIM: 134820), fibrinogen beta chain (FGB, MIM: 134830), alpha 2‐HS glycoprotein (AHSG, MIM: 138680), albumin (ALB, MIM: 103600), alpha‐1‐microglobulin/bikunin precursor (AMBP, MIM: 176870), serpin family A member 1 (SERPINA1, MIM: 107400), apolipoprotein H (APOH, MIM: 138700), inter‐alpha‐trypsin inhibitor heavy chain 2 (ITIH2, MIM: 146640), histidine‐rich glycoprotein (HRG, MIM: 142640), and transthyretin (TTR, MIM: 176300), which mostly were serum proteins and plasma proteins, mainly functioning in coagulation, protease inhibitors, transport or inflammatory regulation 25–33 …”
Section: Resultsmentioning
confidence: 99%
“…The hub genes were fibrinogen alpha chain (FGA, MIM: 134820), fibrinogen beta chain (FGB, MIM: 134830), alpha 2-HS glycoprotein (AHSG, MIM: 138680), albumin (ALB, MIM: 103600), alpha-1microglobulin/bikunin precursor (AMBP, MIM: 176870), serpin family A member 1 (SERPINA1, MIM: 107400), apolipoprotein H (APOH, MIM: 138700), inter-alpha-trypsin inhibitor heavy chain 2 (ITIH2, MIM: 146640), histidine-rich glycoprotein (HRG, MIM: 142640), and transthyretin (TTR, MIM: 176300), which mostly were serum proteins and plasma proteins, mainly functioning in coagulation, protease inhibitors, transport or inflammatory regulation. [25][26][27][28][29][30][31][32][33] To decide the significant biomarkers, the KM survival curve was constructed for the top 10 hubs. Only the expression of AHSG was found to be associated with chRCC.…”
Section: Ppi Network and The Hub Genes Analysismentioning
confidence: 99%
“…A meta-analysis showed that low pretreatment AGR was related poor prognosis in cancers (18). Sütçüoğlu et al showed that low AGR was related with increased risk of mortality in febrile neutropenia (19).…”
Section: Discussionmentioning
confidence: 99%